Total MRI small vessel disease burden in cerebral amyloid angiopathy: a concept validation imaging-pathological study - Charidimou, Andreas (JAMA Neurol, 2016)
IMPORTANCE: Cerebral amyloid angiopathy (CAA) is characteristically associated with MRI biomarkers of small vessel brain injury, including strictly lobar cerebral microbleeds, cortical superficial siderosis, centrum semiovale perivascular spaces, and white matter hyperintensities. Although these neuroimaging markers reflect distinct pathophysiological aspects in CAA, no studies to date have combined these structural imaging features to gauge total brain small vessel disease burden in CAA. OBJECTIVES: To develop a composite score to capture the total brain MRI burden of small vessel disease in CAA, based on the most salient imaging signatures of the disease. Furthermore, to explore whether this score contributes independent and complementary information about CAA severity, defined as intracerebral hemorrhage (ICH) during life or bleeding-related neuropathologic changes. DESIGN: MRI-pathological study. SETTING: Single centre neuropathological CAA cohort based on eligible patients from the Massachusetts General Hospital (MGH) (1997–2012). PARTICIPANTS: Patients with both pathological evidence of CAA (i.e. any presence of CAA from routinely collected brain biopsy, biopsy at hematoma evacuation or autopsy) and available brain MRI sequences of adequate quality including T2-weighted, T2*-weighted gradient-recalled echo (T2*-GRE) and/or SWI and FLAIR sequences. MAIN OUTCOMES AND MEASURES: Brain MRIs were rated for lobar cerebral microbleeds, cortical superficial siderosis, centrum semiovale perivascular spaces and white matter hyperintensities. All four MRI lesions were incorporated into a pre-specified ordinal total small vessel disease score ranging from 0–6 points. Associations with severity of CAA-associated vasculopathic changes (fibrinoid necrosis and concentric splitting of the wall), clinical presentation, ICH number and other imaging markers not included in the score were explored using logistic and ordinal regression. RESULTS: In multivariable ordinal regression analysis, severity of CAA-associated vasculopathic changes (OR: 2.40; 95%CI: 1.06–5.45; p=0.035) and CAA presentation with symptomatic ICH (OR: 2.23; 95%CI: 1.07–4.64; p=0.033) were independently associated with the total MRI small vessel disease score. The score was associated with small acute diffusion-weighted imaging lesions and posterior white matter hyperintensities in adjusted analyses. CONCLUSIONS AND RELEVANCE: Our study provides evidence for concept validity of a total MRI small vessel disease score in CAA. After further validation, this approach can be potentially used in prospective clinical studies.